Development of capitals in integrated reporting and weighting representative indicators with entropy approach - Aras, Guler; Mutlu Yildirim, Filiz (EMERALD GROUP PUBLISHING LTD, 2022)
Purpose In integrated reporting, financial and non-financial performance is presented interactively, as the value creation abilities of corporations are shaped via capitals, the importance of the topic increases day by day. In addition to this, differentiation of importance of basic and sub-dimensions representing capitals between institutions leads to questions on which weight these should take place. From this point, this paper aims to develop capitals in integrated reporting and to weight the indicators representing them. Design/methodology/approach In this study, first, to ensure that each component of capital is included in integrated reporting, governance capital has been added to capitals, which are identified in the international integrated reporting framework (the framework). Then, weights of each capital dimension and indicators within these dimensions have been determined in a banking sector example with the entropy method. Findings Including the 2014-2017 period, an efficient weight assessment approach with the entropy method has been presented and it was observed that the most weighted element is the intellectual capital. Research limitations/implications The limitations of this study are the lack of an agreed general indicator framework for indicators representing multiple capitals in integrated reporting, each bank's data disclosure of different indicators and differentiation of the shared data between sources. Practical implications This study guides the weighting studies necessary for integrated performance measurement. Social implications It is foreseen that this study will be effective in the development of integrated thinking and this effect will contribute to the overall functioning of all sectors beyond the banking sector, which is the application area of the study. Originality/value The study is the first original study in the literature in terms of providing a new dimension by adding the governance capital to the capitals defined in the Framework.
Keywords: Corporate governance; Intellectual capital; Banking sector; Integrated reporting; Entropy method; Multiple capitals; MODERATING ROLE; SERVICE FIRMS; SUSTAINABILITY; PERFORMANCE; DISCLOSURE; RESOURCE; BANKING; MANAGEMENT; Business & Economics